2020
DOI: 10.3389/fphar.2020.00344
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein S6 Hypofunction in Postmortem Human Brain Links mTORC1-Dependent Signaling and Schizophrenia

Abstract: The mechanistic target of rapamycin (also known as mammalian target of rapamycin) (mTOR)-dependent signaling pathway plays an important role in protein synthesis, cell growth, and proliferation, and has been linked to the development of the central nervous system. Recent studies suggest that mTOR signaling pathway dysfunction could be involved in the etiopathogenesis of schizophrenia. The main goal of this study was to evaluate the status of mTOR signaling pathway in postmortem prefrontal cortex (PFC) samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 82 publications
(124 reference statements)
1
10
2
Order By: Relevance
“…Increased mTORC1 activity and glycolysis was also seen in olanzapine [ 60 ], a second-generation antipsychotic, similar to what we found in cells treated with risperidone. In contrast to our results, Ibarra-Lecue et al have shown that only haloperidol, and not risperidone, increased the activation of the AKT/mTORC1 pathway [ 55 ]. However, a drug-regulated transcriptional study by Korostynski et al revealed that second-generation antipsychotics, including risperidone, strongly induced the transcription of mTOR pathway-related genes [ 61 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Increased mTORC1 activity and glycolysis was also seen in olanzapine [ 60 ], a second-generation antipsychotic, similar to what we found in cells treated with risperidone. In contrast to our results, Ibarra-Lecue et al have shown that only haloperidol, and not risperidone, increased the activation of the AKT/mTORC1 pathway [ 55 ]. However, a drug-regulated transcriptional study by Korostynski et al revealed that second-generation antipsychotics, including risperidone, strongly induced the transcription of mTOR pathway-related genes [ 61 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Cell proliferation is another function attributed to mTOR activity, while cells with strong mTOR inhibition have reduced viability [ 54 ]. Finally, mTORC1-dependent signaling has been linked in post-mortem animal studies with schizophrenia, specifically the hypofunction of the ribosomal protein S6 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, metabolism of RNA was consistently deregulated in SCZ/c in every functional comparison. Although prior studies have found deregulations in ribosomal and RNA-related proteins in human samples from SCZ patients [53,54], our data revealed functional differences in metabolism of RNA exclusively linked to the coexistence of cannabis consumption and SCZ. According to REACTOME, MTREX and ZNF326 are involved in the same step of pre-mRNA processing prior to protein translation.…”
Section: Discussioncontrasting
confidence: 90%
“…In addition, drugs of abuse and antipsychotics also regulate RPS6 phosphorylation [ 392 ]. Interestingly, the p-RPS6 level in schizophrenia is reduced [ 393 ]. Elevated expression or phosphorylation of RPS6 has also been found in multiple sclerosis [ 394 ].…”
Section: Functions Of Rps6mentioning
confidence: 99%